Studi Awal Pemanfaatan Rumput Laut dan Daun Cincau Hijau Sebagai Kandidat Bahan Alternatif untuk Injeksi Polimer EOR - Huljannah, Miftah; Lestari, Fitra Ayu; Erfando, Tomi (Diponegoro University, 2020)
The declining in production can occur because wells that have been producing for a long time are no longer able to lift oil to the surface in primary and secondary ways. Therefore, tertiary methods such as chemical injection like polymer flooding were carried out. Polymers commonly used in flooding polymers are divided into three namely synthetic polymers, biopolymers, and natural polymers. Natural polymers have abundant sources such as seaweed and grass jelly. This study was aimed to identify alternative renewable polymers as flooding polymer materials by knowing initial characteristics such as viscosity, compatibility and the effect of shear rates. This test wass carried out by an experimental method with several stages, namely drying, crushing to powder, and making polymers that were dissolved into brines that have different salinity. Then the polymer was allowed to stand for more than 24 hours until it was tested. The material tested was seaweed, grass jelly, and biopolymer xanthan gum as a comparison. The parameters used are polymer concentrations of 1000 ppm, 2000 ppm and 3000 ppm with each salinity of 3000 ppm, 9000 ppm and 15000 ppm. The test results showed that the characteristics of natural polymers were the same as biopolymers, the viscosity decreased as the brines salinity increased .The absence of sedimentation resulted from Seaweed and grass jellyÂ solution and formation water indicated that the polymers had good compatibility andÂ shear rate test has shown that the polymers are psuodoplastic.